1995
DOI: 10.1093/clinchem/41.4.564
|View full text |Cite
|
Sign up to set email alerts
|

6 alpha-biotinylated estrone: novel tracer in competitive chemiluminescence immunoassay of estrone in serum

Abstract: We describe the development and validation of a labeled-hapten competitive immunoassay for determining total estrone in serum. For the hapten tracer we use the 6 alpha-biotinylated estrone derivative, 3-hydroxyestra-1,3,5(10)-trien-17-one 6 alpha-N-(epsilon-biotinyl)aminocaproamide (Bio-E1). A specific polyclonal rabbit anti-estrone antibody is indirectly bound via an immobilized donkey anti-rabbit antibody on microtiter plate wells. The amount of Bio-E1 bound is then measured with streptavidin-horseradish per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Recently, we showed that the introduction of a biotin label to E1 at the ring position 6R and to T at the position 7R leads to negligible alterations in comparison to the structure of the respective steroidal hapten (Luppa et al, 1994(Luppa et al, , 1996. These characteristics allow sensitive and reproducible determinations of E1 and T over large dynamic ranges (Luppa et al, 1995(Luppa et al, , 1997. In addition, the 7R-C 11 -Bio-T tracer, which we applied in the chemiluminescence immunoassay, provided higher specificity through a better availability of the critical antigen sites which is in accordance with suggestions made by Fra ´nek (1987).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that the introduction of a biotin label to E1 at the ring position 6R and to T at the position 7R leads to negligible alterations in comparison to the structure of the respective steroidal hapten (Luppa et al, 1994(Luppa et al, , 1996. These characteristics allow sensitive and reproducible determinations of E1 and T over large dynamic ranges (Luppa et al, 1995(Luppa et al, , 1997. In addition, the 7R-C 11 -Bio-T tracer, which we applied in the chemiluminescence immunoassay, provided higher specificity through a better availability of the critical antigen sites which is in accordance with suggestions made by Fra ´nek (1987).…”
Section: Discussionmentioning
confidence: 99%
“…By use of biotinylated steroids as stable immunochemical probes in connection with streptavidin-conjugated reporter enzymes, it is possible to develop a series of competitive immunoassays for the determination of individual steroid concentrations in biological fluids (9). In the process of establishing such an assay for total testosterone, we synthesized a 7R-biotinylated testosterone derivative (7R-Bio-T).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the chemical structure of the spacer has a relevant influence on the process of antibody recognition: the structure must be similar to the linkage used in the immunization procedure. A competitive, nonradioactive immunoassay for E1 was set up with this new kind of steroid tracer (9), taking advantage of the high biotin affinity to a streptavidin reporter enzyme conjugate.…”
Section: Introductionmentioning
confidence: 99%
“…Various biotinylated steroids have been used as an excellent tracer for analyzing specific ligandbinding events of steroids and antisteroid antibodies. [22][23][24] We have previously achieved the receptor binding assay for benzodiazepine drugs based on a solid-phase avidin-biotin binding assay. 25 The same principle was applied to the immunoassay for 17b-estradiol and estradiol antibody in this study.…”
Section: Introductionmentioning
confidence: 99%